2018
DOI: 10.1002/art.40556
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Expansion and Function of Follicular Helper T Cell Subsets in IgG4‐Related Disease

Abstract: ObjectiveTo determine the number and function of follicular helper T (Tfh) cell subsets in IgG4‐related disease (IgG4‐RD).MethodsMononuclear cells from the peripheral blood and involved tissue of patients with IgG4‐RD were assessed for Tfh cells and their subsets, and levels of B cell lymphoma 6 (Bcl‐6), B lymphocyte–induced maturation protein 1 (BLIMP‐1), and interleukin‐21 (IL‐21) messenger RNA (mRNA). Immunohistochemical and immunofluorescence techniques were used to assess the involved tissue of patients t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 30 publications
3
73
0
1
Order By: Relevance
“…In addition, there are some studies published in Chinese which showed iguratimod treatment was effective for primary Sjögren's syndrome and patient's serum Ig was decreased as well. As we know, one of the most prominent characteristics of IgG4‐RD is activation of B cells and plasmablast cells, which excrete large amount of serum IgG and IgG4 . Therefore, we think that iguratimod treatment may be effective in the treatment of IgG4‐RD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are some studies published in Chinese which showed iguratimod treatment was effective for primary Sjögren's syndrome and patient's serum Ig was decreased as well. As we know, one of the most prominent characteristics of IgG4‐RD is activation of B cells and plasmablast cells, which excrete large amount of serum IgG and IgG4 . Therefore, we think that iguratimod treatment may be effective in the treatment of IgG4‐RD.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoglobulin G4‐related disease (IgG4‐RD) is a newly defined chronic fibro‐inflammatory disorder characterized by elevated serum IgG4 levels, tumefactive lesions with a dense lymphoplasmacytic infiltration rich in IgG4 positive plasma cells and storiform fibrosis of related organs . Glucocorticoids are the first‐line agents for the treatment of IgG4‐RD; however, in order to maintain long‐term disease stability and avoid disease relapse, usually glucocorticoids maintenance therapy should last for a long period, which may induce various glucocorticoid‐associated adverse reactions.…”
Section: Introductionmentioning
confidence: 99%
“…And the independents introduced in IgG4-RD CS prediction model are supported by previous evidences. Such abnormalities of specific lymphocyte subsets are present in the blood of patients with IgG4-RD, including CD4+ cytotoxic T lymphocytes (CTL), follicular helper T (Tfh) cell, CD19+CD24−CD38hi plasmablasts/ plasma cells, and so on [32,[40][41][42][43][44], and the role of Eosinophil in IgG4-RD has been reported in previous studies [15,16,45,46]. Finally, after we performed cluster analysis in different genders, IgG4-RD CS presented superior ability to guide treatment in female patients.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating Tfh1 and Tfh2 cells expressing programmed cell death protein 1 (PD1) are expanded in patients with IgG4-RD and correlate with disease activity, plasmablast numbers, and serum concentrations of IgG4 and interleukin 4 444546. PD1 positive Tfh2 cells drive IgG4 class switch in vitro, enhance proliferation of IgG4 committed B cells, and facilitate differentiation of naive B cells into plasmablasts/plasma cells, resulting in increased IgG4 secretion 464748. Activated Tfh cells expressing interleukin 4 and interleukin 21 are also found in tertiary lymphoid structures of IgG4-RD affected tissues and likely contribute to germinal center formation 1495051.…”
Section: Overview Of Disease Pathophysiologymentioning
confidence: 99%